If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + 5m = 50 + 6m Solving 17 + 5m = 50 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 17 + 5m + -6m = 50 + 6m + -6m Combine like terms: 5m + -6m = -1m 17 + -1m = 50 + 6m + -6m Combine like terms: 6m + -6m = 0 17 + -1m = 50 + 0 17 + -1m = 50 Add '-17' to each side of the equation. 17 + -17 + -1m = 50 + -17 Combine like terms: 17 + -17 = 0 0 + -1m = 50 + -17 -1m = 50 + -17 Combine like terms: 50 + -17 = 33 -1m = 33 Divide each side by '-1'. m = -33 Simplifying m = -33
| 3b^3=81 | | 9x^2-196y^2= | | x^2-30x+150=0 | | 2x(28x^2-27x+5)=0 | | 6x^4-24x^3-2x^2+8x=0 | | 3x-9+x=27 | | 4(5m+6)-8=336 | | 8x-(5-4x)=6-(4x+9) | | x^2-30x+200=0 | | 3c-2c+c= | | -4x+15=59 | | 15x^2-16x+11= | | -4+19(y+2)+5(y+2)2= | | 2(x-4)=6x-(2x-1)2 | | (-4+-1x)(1+-5x)= | | 6x^2y-38xy^2+56y^3= | | 10x^2-66xy-28y^2= | | 4y^3+8y^2+3y= | | 3a^2-10ab-32b^2= | | 5a^2-6ab-32b^2= | | 16y^2-24y+9= | | 4x^2+5x+1= | | y=2-x^2 | | -3(-4-6y)+7(-y+6)=-8 | | -3(-4-6y)7(-y+5)=-8 | | 4=2/3(x+3) | | F^2+25+150=0 | | 1.8+2.8=2.5+2.1 | | 9t-15+=-18 | | 4X-2=158-4X+4 | | 5x^2+9y^2=3 | | 7-55u=-43 |